Charateristics and reasons for diabetic-defaulters between primary care clinics and diabetic specialist clinic: A prospective cohort study in Kuantan, Malaysia - Abdullah, Fa’iza; Tin, Myo Han; Md Aris, Mohd Aznan; Osman, Iskandar Firzada (Kulliyyah of Medicine, International Islamic University Malaysia (IIUM), 2016)
Defaulted appointment in diabetic clinics is a great concern as it affects disease controlled and complications. Geographical location, clinic-types and quality of health services provided are known determinant reasons for defaulting. Thus, this study aimed to identify characteristics and reasons for default between diabetic-patients at public-primary-care-clinics (PPCCs) and public-hospital-diabetic-specialist-clinic (DS-OPD). Methods: A prospective one-year-cohort study was conducted among 405 diabetic patients from two PPCCs and DS-OPD in Kuantan (2015-2016). There were 2-point visits (at 6-month and 12-month) assessing follow-up appointments within one year. Defaulter is defined by at least one-time defaulted either at 6-month or 12-month. Regular-attendees were included as control. Type-1-DM-patients, missing-records, known-deceased and transfer-out cases were excluded. Background socio-demographic data of diabetic-defaulters were collected from DM-records and reasons for defaulting were traced via 3-times-telephone contacts which 51.6% diabetic-defaulters responded. A stratified cross-analysis was done to compare the prevalence and characteristics between defaulters and regular attendees. Reasons for defaults were analyzed using open-ended-questions analysis method. Results: Prevalence of defaulters was 18% (73/405); higher prevalence was found in DS-OPD than PPCCs (32.4% vs 10.3%). Gender, race, age, education, occupation and the duration of DM were not significantly different between defaulters and regular-attendees at DS-OPD. However, self-employment (25.9%), housewives (25.9%), aged less than 45-years (33.3%) and≥ 55 years-old (44.4%) were significant defaulters in PPCCs. Significant different of reasons for default found at DS-OPD compare to PPCCs for postponing the date (54.5% vs 12.5%), while refusing treatment/used alternative medicine (18.2% vs 43.8%); and moved-out/transferred/referred cases (27.3% vs 31.2%) were more in PPCCs. Conclusions: Distinctive characteristics and diverse reasons for default between DS-OPD and PPCCs among diabetic-patients fortified to set tailored remedial to reduce defaulter-rate in different clinic.